2013
DOI: 10.3892/mmr.2013.1320
|View full text |Cite
|
Sign up to set email alerts
|

Low-grade inflammation in the rectum of patients with sporadic irritable bowel syndrome

Abstract: Abstract. Irritable bowel syndrome (IBS) is a common chronic gastrointestinal disorder that considerably reduces quality of life and is an economic burden on society. The pathogenesis of IBS is unknown. However, intestinal low-grade inflammation has been proposed as one of the factors contributing to the development of IBS. The present study aimed to examine the possible occurrence of low-grade inflammation in the rectum of patients with sporadic IBS. In total, 50 patients (42 females and 8 males with an avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…Twenty‐two studies which analyzed colonic mast cell and/or lymphocyte counts were included in this meta‐analysis . The studies included a total of 706 patients with IBS and 401 controls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty‐two studies which analyzed colonic mast cell and/or lymphocyte counts were included in this meta‐analysis . The studies included a total of 706 patients with IBS and 401 controls.…”
Section: Resultsmentioning
confidence: 99%
“…The above mentioned physiological balance is affected in GI diseases/disorders such as IBS. Higher mast cell and T cell mucosal infiltration, their state of activity, and cytokine secretion and gene polymorphisms have been proposed to impact bowel physiology and participate in symptom development of IBS . However, these results remain controversial.…”
Section: Introductionmentioning
confidence: 99%
“…In all, 66 articles were identified that provided results on either mucosal or serological immune markers in IBS; 43 reported on mucosal changes, 19 on serological markers and seven on both. Some focused on specific IBS subtypes, including three reported on a comparison of diarrhea‐predominant IBS (IBS‐D) with healthy controls, one compared post‐infection (PI)‐IBS to the general population, and three limited their evaluation to a comparison between PI‐IBS and IBS‐D .…”
Section: Resultsmentioning
confidence: 99%
“…El-Salhy et al [71] reported that rectal biopsy specimens taken from patient after Campylobacter gastroenteritis showed increases in leucocytes, lymphocytes, mast cells and endocrine cells. Another study reported that 3 mo post-gastroenteritis, patients who had PI-IBS continued to increase their chronic inflammatory cell counts, while those in healthy controls returned to normal levels [72] .…”
Section: Inflammationmentioning
confidence: 97%